Korelasi Gaya Belajar Visual, Auditori, dan Kinestetik Dengan Pemahaman Materi Pendidikan Agama Islam Kelas XI di SMK Negeri 1 Kebumen - Fitriasih, Faizah; Arifah, Umi (Tarbi: Jurnal Ilmiah Mahasiswa, 2025)
This study aims to determine the relationship between visual, auditory, and kinesthetic learning styles and students' level of understanding of Islamic Religious Education material in eleventh-grade students at SMK Negeri 1 Kebumen. The method used was quantitative with a correlational design. The study subjects included all 504 eleventh-grade students, with sampling conducted using a simple random sampling technique. Referring to Arikunto's opinion, if the population is less than 100, then all students should be included in the sample. However, if the population is large enough, the sampling can range from 10% to more than 50%, depending on the researcher's capabilities and field conditions. In this study, the researchers selected a sample of 20% of the population, or 108 students. Data collection was conducted using a questionnaire containing indicators of visual, auditory, and kinesthetic learning styles (VAK), as well as an instrument to measure understanding of Islamic Religious Education material designed based on the characteristics of each learning style. The collected data were analyzed using various statistical tests, such as instrument validity and reliability tests, as well as prerequisite tests including normality, linearity, and Pearson Product Moment correlation tests. The analysis results showed a very strong relationship between learning styles and material comprehension, with the respective contributions of: visual learning styles at 20,8%, auditory at 23,1%, and kinesthetic at 21,3%.